STRUKTUR POPULASI DAN POLA DISTRIBUSI PALA (Myristica fragrans Houtt) PADA PERKEBUNAN PALA DI DUSUN MANGKOBATU BANDA NEIRA MALUKU TENGAH - Lawansuka, Gielldy; Tuhumuri, Evelin; Sahertian, Dece Elisabeth (Biofaal Journal, 2024)
Nutmeg (Myristica fragrans Houtt) is a native plant of Indonesia and endemic to the Banda Islands, Maluku. Nutmeg plantations are scattered across various locations in Banda Neira, one of which is in Mangkobatu Village. The population structure in nutmeg plantations is essential for predicting the future regeneration of trees to replace the old ones. This study aims to describe the population structure and analyze the distribution pattern of nutmeg in the plantations of Mangkobatu Village, Banda Neira, Central Maluku. The research used the quadrat method to count individual nutmeg trees for analysis of density, sex ratio, and distribution patterns. The results show that the population structure of nutmeg in the plantations of Mangkobatu Village consists of seedling stages with a density of 250 individuals/ha, sapling stages with 380 individuals/ha, pole stages with 190 individuals/ha, and mature trees with 68.75 individuals/ha. The population structure forms a bell-shaped polygon diagram. The sex ratio of nutmeg in the plantations of Mangkobatu Village is 1:27, which does not align with the recommended ratio for nutmeg plantations. The distribution pattern of nutmeg at the seedling stage is clumped (Ip = 1), while at the sapling (Ip = -0.464), pole (Ip = -0.357), and mature tree (Ip = -0.567) stages, the distribution is uniform.